Transport and Recovery of Gilthead Seabream (Sparus aurata L.) Sedated With Clove Oil and MS-222: Effects on Stress Axis Regulation and Intermediary Metabolism - Jerez-Cepa, Ismael; Fernández-Castro, Miriam; Del Santo O'Neill, Thomas Julian; Martos-Sitcha, Juan Antonio; Martínez-Rodríguez, Gonzalo; Mancera, Juan Miguel; Ruiz-Jarabo, Ignacio (Frontiers in Physiology, 2019)
Transport processes between aquaculture facilities activate the stress response in fish. To deal with these situations, the hypothalamic-pituitary-interrenal (HPI) axis releases cortisol, leading to an increase in circulating energy resources to restore homeostasis. However, if the allostatic load generated exceeds fish tolerance limits, stress-related responses will compromise health and welfare of the animals. In this context, anesthetics have arisen as potential agents aiming to reduce negative effects of stress response. Here we assessed the effects of a sedative dose of clove oil (CO) and MS-222 on hallmarks involved in HPI axis regulation and energy management after simulated transport, and further recovery, in gilthead seabream (Sparus aurata L.) juveniles. Fish were placed in a mobile setup of water tanks where transport conditions were simulated for 6 hours. Sedation doses of either CO (2.5 mg L-1) or MS-222 (5 mg L-1) were added in the water tanks. A control group without anesthetics was also included in the setup. Half of the animals (n = 12 per group) were sampled immediately after transport, while remaining animals were allowed to recover for 18 h in clean water tanks and then sampled. Our results showed that the HPI axis response was modified at peripheral level, with differences depending on the anesthetic employed. Head kidney gene-expressions related to cortisol production (star and cyp11b1) matched concomitantly with increased plasma cortisol levels immediately after transport in CO-sedated fish, but these levels remained constant in MS-222-sedated fish. Differential changes in the energy management of carbohydrates, lipids and amino acids, depending on the anesthetic employed, were also observed. The use of CO stimulated amino acids catabolism, while MS-222-sedated fish tended to consume liver glycogen and mobilize triglycerides. Further studies, including alternative doses of both anestethics, as well as the assessment of time-course HPI activation and longer recovery periods, are necessary to better understand if the use of clove oil and MS-222 is beneficial for S. aurata under these circumstances.